Guía de educación ambiental como recurso didáctico en la identificación de los principales contaminantes de la parroquia Sicalpa del Cantón-Colta para el cuidado y protección de los ecosistemas. - Guzmán Rodríguez, Anahí Viviana (2023)
Ecosystems provide innumerable benefits to man, such as housing and food. However, a significant challenge faced by the residents of the Sicalpa parish of the Colta canton is to identify the contaminants that deteriorate their ecosystems, which come from anthropic and natural factors, which generally represent the main sources of pollution in these natural environments. The objective of this study focused on proposing environmental education as a learning strategy that allows for addressing issues related to environmental pollution and the deterioration of ecosystems. For this reason, an environmental education guide was implemented as a teaching resource to promote its care and protection. The research methodology responded to a mixed, qualitative, and quantitative approach with a nonexperimental design. The type of research was descriptive, exploratory, field, and bibliographic, and the methods used to observe and analyze the data were inductive, deductive, and analysis-synthesis. For data collection, a survey was applied to 52 community members from the Sicalpa parish of the Colta canton, and also an interview with three leaders of the communities belonging to the parish. After the analysis and interpretation of results, it was concluded that implementing an environmental education guide allows residents to become aware of the importance of caring for and protecting the moor.